Relações entre interesses, interação social e aprendizagem na Educação a Distância: estudo de casos no Curso de Licenciatura em Matemática a Distância da Universidade Federal de Pelotas - Hallwass, Lia Cristiane Lima (2010)
This Master‟s dissertation aimed to contribute to the understanding of the learning process in Distance Education (DE). Currently, DE is a widespread educational modality favoring access to higher education. Thus, I consider fundamental to know its characteristics and the processes involved in it, in particular to know how individuals learn in this modality and what factors are associated with such learning. The objective of this investigation was to examine the influence of interests and social interactions on the learning process of students enrolled in the Distance Mathematics Teacher Training Course from the Federal University of Pelotas/RS (DMTTC / UFPel). The study used, as its theoretical basis, the Historical-Cultural perspective, proposed by Lev S. Vygotsky, due to the fact that, in the same way as Distance Education, this perspective emphasizes the importance of social interactions for learning, thus offering valuable support to the exploration of the proposed theme. The research has adopted a qualitative approach (case-studies), having a descriptive and exploratory character. The cases analyzed have been selected from the group of students enrolled in the second phase of the DMTTC - Open University of Brazil Program (DMTTC/ UAB 2), which were about 350, divided into seven poles distributed around Rio Grande do Sul. Through online questionnaires, it was possible to trace the profile of this group of students as well as the group enrolled in one of the poles of that phase of the Program, Santa Vitoria do Palmar (SVP). These profiles were used for the intentional selection of case-studies participants and as a context for the interpretation of the data obtained through such studies. The subjects were two students (one female and one male). They participated in distance semi-structured interviews (by telephone), during which information was obtained on their initial and subsequent interests and expectations related to the course, their interactions with peers, teachers and tutors, and their performance. Although the findings of this research cannot be generalized to all Distance Education students, due to its qualitative nature, the thematic analysis of the collected data suggests that strong interests and the intensity of interaction between peers influenced learning and performance of the students. They also suggest that face-to-face interactions were fundamental to promote such good performance.